2022
DOI: 10.1038/s41467-022-33356-z
|View full text |Cite
|
Sign up to set email alerts
|

Exportin 4 depletion leads to nuclear accumulation of a subset of circular RNAs

Abstract: Numerous RNAs are exported from the nucleus, abnormalities of which lead to cellular complications and diseases. How thousands of circular RNAs (circRNAs) are exported from the nucleus remains elusive. Here, we provide lines of evidence to demonstrate a link between the conserved Exportin 4 (XPO4) and nuclear export of a subset of circRNAs in metazoans. Exonic circRNAs (ecircRNAs) with higher expression levels, larger length, and lower GC content are more sensitive to XPO4 deficiency. Cellular insufficiency of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
27
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 35 publications
(34 citation statements)
references
References 81 publications
0
27
0
Order By: Relevance
“…Since circRNAs have no free ends, they must be exported via a different mechanism. In support, our recent study has demonstrated that the evolutionarily conserved receptor Exportin-4 (XPO4) directly binds to a subset of circRNAs, but not their linear counterparts, to facilitate their nuclear export ( 15 ).…”
Section: Introductionmentioning
confidence: 90%
“…Since circRNAs have no free ends, they must be exported via a different mechanism. In support, our recent study has demonstrated that the evolutionarily conserved receptor Exportin-4 (XPO4) directly binds to a subset of circRNAs, but not their linear counterparts, to facilitate their nuclear export ( 15 ).…”
Section: Introductionmentioning
confidence: 90%
“…Therefore, the process of circRNA nuclear export is crucial for its function. Study has shown that efficient circRNA nuclear export is a previously unappreciated layer of regulation which is critical to normal physiological function ( 77 ). The abnormalities in circRNA nuclear export lead to physiological defects ( 78 , 79 ).…”
Section: Discussionmentioning
confidence: 99%
“…Decreases of ADAR levels in Drosophila due to high temperature will also lead to increased RNA circularisation [ 161 ]. Different to the linear mRNAs with the lack of 5′ and 3′ UTRs, the GW182-mediated circRNA degradation and the pathway controlling circRNA export from the nucleus are also conserved between Drosophila and human [ 165 , 166 , 167 , 168 ].…”
Section: Circrna In Drosophilamentioning
confidence: 99%